The investment portfolio for the scheme of Amanah Saham Bumiputera (ASB) for the year 2006 to 2008: the case for Permodalan Nasional Berhad (PNB) / Mohd Izuan Suleiman - Suleiman, Mohd Izuan (Faculty of Business and Management, 2009)
This report paper is mainly to study on “The investment portfolio for the scheme of Amanah Saham Bumiputera (ASB) for the year 2006 to 2008: the case for Permodalan Nasional Berhad”. throughout this case study paper, we will analyze at which companies the funds from scheme Amanah Saham Bumiputera (ASB) has to be channeled by Permodalan Nasional Berhad (PNB). This paper will also analyze how many companies been invested each year, the types of companies and trends of selecting the companies. Besides, from this case study also, we will see the most suitable selecting companies done by Permodalan Nasional Berhad (PNB) by using the dividend and bonus as benchmark in three years back. The most significant of this paper is where the ideas generated, recommendation and justification part, where almost of the information are generated from the annual report of Amanah Saham Bumiputera (ASB) for year 2006 until 2008 with supplement of table and also pie chart.